Indian Givers: What Indigenous Peoples Have Contributed to International Human Rights Law - S. James Anaya (Washington University Journal of Law & Policy, 2006)
The remarks that follow summarize how the claims of indigenous peoples have not only taken advantage of changes in the character of international law but have also contributed to those changes, particularly in the area of human rights. These changes are beneficial not just for indigenous peoples themselves but the humanity more broadly. Part I describes the nature of disparate international legal arguments employed by indigenous peoples and how those arguments have tended toward a human rights discourse. Part II discusses specific ways in which the indigenous human rights discourse has contributed to the evolution of international human rights law.
Keywords: Indians of North America; International law; Human rights; Native Americans; Sovereignty; International; United States